The lasting legacy of the European Reformation of the 16th century: Protestant foundations of modern educational reasoning. Issue 2 (3rd April 2021) - Tröhler, Daniel
ABSTRACT: This article argues that crucial elements of the three most important theoretical models of twentieth-century education can be traced back to three Protestant denominations that were developed in Europe in the sixteenth and seventeenth centuries. First, rather than to look in depth at the Protestant Reformers' own educational ideas, the paper examines their perceptions of how the social or political order should be governed as appropriate for salvation. It then shows how educational models became possible in the context of the three Protestant denominations as they morphed across time and space: German Lutheranism and how it eventually gave rise to the theory of Bildung, which goes hand in hand with the dual world view of Lutheranism; the political theology of Zwinglianism and how it was developed into the Congregational religious order in England and led to the ideal of the virtuous and cooperative citizen in American pragmatism; and Geneva Calvinism and how it was transformed into Presbyterianism in Scotland, its principles of governance, and how it contributed to a certain idea of school organisation that is to be regulated by test psychology and experts.